2001
DOI: 10.1063/1.1328068
|View full text |Cite
|
Sign up to set email alerts
|

Model for the aggregation state of living anionic polymers

Abstract: Temperature-dependent micellar structures in poly(styrene-b-isoprene) diblock copolymer solutions near the critical micelle temperature

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
21
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 55 publications
4
21
0
Order By: Relevance
“…The activation energy ÁE is considerably smaller than the bare binding energy calculated with quantum chemical methods, 34 ÁE ðbareÞ ¼ $ 150 kJ/mol for a tetramer of allyllithium. This difference seems to be a natural consequence of the cooperativity of the Li-Li exchange process: The exchange would occur through formation of the transient aggregates (Figure 11b) without releasing an isolated Li species.…”
mentioning
confidence: 99%
“…The activation energy ÁE is considerably smaller than the bare binding energy calculated with quantum chemical methods, 34 ÁE ðbareÞ ¼ $ 150 kJ/mol for a tetramer of allyllithium. This difference seems to be a natural consequence of the cooperativity of the Li-Li exchange process: The exchange would occur through formation of the transient aggregates (Figure 11b) without releasing an isolated Li species.…”
mentioning
confidence: 99%
“…22 These fused aggregates should be less stable and thus in a higher energy state compared to the tetrameric aggregates (detected in scattering experiments 21,22 as the main component of the aggregates), suggesting a possibility that the fused aggregates, once formed transiently, contribute to the propagation. This possibility is in harmony with quantum chemistry calculations 23,24 that suggest a low probability of the propagation only through the dissociated unimers.…”
mentioning
confidence: 49%
“…For PBLi mainly forming tetrameric aggregates in benzene, 21,22 the NMR data indicated that a thermal exchange of several different Li species occurs in the system and its characteristic time ex depends on the concentration (C) and molecular weight (M) of PBLi. 22 This ex was associated with an activation energy (ÁE ¼ 88 kJ mol À1 ) considerably lower than the energy ÁE C-Li for a C-Li bond dissociation 23 (> 150 kJ mol À1 ). The C-and M-dependencies of ex as well as this ÁE value suggested that the Li-Li exchange occurs mainly through a thermal fusion of the tetrameric aggregates into larger aggregates without forming the dissociated unimers.…”
mentioning
confidence: 99%
“…For monodisperse PBLi chains of the molecular weights M ¼ 2:6 Â 10 3 -9:6 Â 10 3 and the mass concentrations C ¼ 0:016{0:096 g cm À3 fully polymerized in benzene (i.e., after completion of the propagation process), light/neutron scattering experiments 15,16 indicated that the PBLi chains predominantly form the (PBLi) f aggregates with the average aggregation number f ¼ $ 4 (and a very minor fraction of huge aggregates with f ) 4), and a 7 Li NMR experiment 16 revealed that several different Li species coexist in the system and a thermal exchange among these species has a Cand M-dependent characteristic time ex (¼ 0:1{10 s at room temperature). Furthermore, this ex was associated with an activation energy, ÁE ¼ 88 kJ mol À1 , that was considerably lower than the energy ÁE C-Li required for cleaving a C-Li bond 17 (> 150 kJ mol À1 ). The C-and M-dependencies of ex as well as this ÁE value suggest that the Li-Li exchange occurs mainly through a thermal fusion of the f -mer aggregates into a larger aggregate, not through an independent dissociation of respective PBLi chains from the f -mer aggregates.…”
mentioning
confidence: 99%
“…In relation to this point, quantum calculations suggested that the propagation through the independently dissociated single chain is hardly probable. 17,18 The simplest propagation route through the transient 2 f -mer aggregates is shown in Scheme 2.…”
mentioning
confidence: 99%